Structuring by electromagnetic forming and by forming with an elastomer punch as a tool for component optimisation regarding mechanical stiffness and acoustic performance - Psyk Verena; Kurka Petr; Kimme Simon; Werner Markus; Landgrebe Dirk; Ebert Andreas; Schwarzendahl Mathias (Manufacturing Review, 2015)
Ecological and economic reasons are forcing industry to improve efficiency and to save energy and resources. Especially for the automotive and transport industry – but also for all other industrial branches dealing with accelerated masses – lightweight design is a key issue for achieving this goal. In current product designs, insufficient geometric stiffness of the part often prohibits exploiting the full potential of weight reduction offered by modern materials. Ideally adapting the geometry to the load profile by implementing appropriate structures frequently allows wall thickness and weight reduction. At the same time, the acoustic properties can be improved in many cases, because the natural frequency of the modified structure is higher compared to a conventionally-designed structure, thus leading to a reduction of awkward low frequency noise (humming). To enable a target-oriented design, the influence of structures manufactured by elastomer tools and by electromagnetic forming (EMF) was analysed systematically. Knowledge about the influence of the structuring technology and the process parameters on the resulting structure properties and the part performance allows conclusions regarding the optimisation of the part functionality via a suitable selection and design of the process.